2015
DOI: 10.4038/jnsfsr.v43i1.7921
|View full text |Cite
|
Sign up to set email alerts
|

Pre and postharvest practices for quality improvement of table grapes (Vitis vinifera L.)

Abstract: Table grapes (Vitis vinifera L.) rank fourth in the world fresh fruit production after citrus, bananas and apples. In Sri Lanka, grapes are grown in an area of about 100 ha. It is one of the main fruits imported to the country and according to Sri Lanka Customs, 5.1 million kg of grapes worth Rs. 1.1 billion were imported in the year 2012. These imports can be significantly reduced as there is ample scope to produce grapes locally in the land available in the North and East of Sri Lanka. The crop thrives well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 17 publications
1
17
0
Order By: Relevance
“…did not lead to a complete absence of gray mold in the grapes, which can also be influenced by the natural occurrence of the fungus and the types of packaging employed [29][30][31]. The different plastic liners evaluated had no influence on this feature in the periods evaluated, however, it was found that the bunches submitted to a combination of factors displayed a lower mean incidence of gray mold compared to those in the additional treatment, which confirmed the need for SO 2 -generating pads in the control of gray mold of 'Benitaka' table grapes during cold storage [4].…”
Section: Natural Occurring Infection Of Gray Moldmentioning
confidence: 86%
See 1 more Smart Citation
“…did not lead to a complete absence of gray mold in the grapes, which can also be influenced by the natural occurrence of the fungus and the types of packaging employed [29][30][31]. The different plastic liners evaluated had no influence on this feature in the periods evaluated, however, it was found that the bunches submitted to a combination of factors displayed a lower mean incidence of gray mold compared to those in the additional treatment, which confirmed the need for SO 2 -generating pads in the control of gray mold of 'Benitaka' table grapes during cold storage [4].…”
Section: Natural Occurring Infection Of Gray Moldmentioning
confidence: 86%
“…The grape productive chain is very demanding in terms of preserving fruit quality. Additionally, maintaining the characteristics of harvested grapes and enabling an increase in shelf-life is important as the fruit is subjected to long storage periods before reaching its final destination, and there are risks of various postharvest losses [4]. Grapes are exposed to different conditions between harvesting and consumption.…”
Section: Introductionmentioning
confidence: 99%
“…The bunch of 'Italia' grapes was adequate with respect to visual appearance, quality, flavor, color, firmness, and shape of the berries because of the limited water loss and absence of stem browning. These are important quality characteristics that comprise both bunch as well as berry properties, and these include phytosanitary conditions, uniform bunch color, bunch mass, size and shape, stem quality, berry size and shape, firmness, and SS and TA content [27].…”
Section: Discussionmentioning
confidence: 99%
“…Grape is one of the most commonly consumed fruits in the world both as fresh fruit (table grape) and processed fruit such as, wine, grape juice, molasses, and raisins. Department of Agriculture, Sri Lanka, recommended that there are mainly five local grape varieties, namely, Israel Blue, Cardinal, Black Muscat, which are table varieties; Muscat MI, which can be used as both table and wine variety and French MI which is a wine variety [1,2].…”
Section: Introductionmentioning
confidence: 99%